A comparison between genetic portraits of normal osteoblasts and osteosarcoma cell lines - Palmieri Annalisa; Pezzetti Furio; Brunelli Giorgio; Ilaria Zollino; Carinci Francesco (Wolters Kluwer Medknow Publications, 2009)
Background: Osteosarcoma (OS) is the most frequent malignant bone tumor occurring in young patients in the first two decades of life. Metastases are the cause of 90% of cancer deaths for patients with OS. OS of the jaw is rare and aggressive malignancy constitutes approximately 5-13% of all cases of skeletal OS. Chemotherapy plus surgery are the first choice for treatment. Aims : Because OS cell lines (OCLs) should share a common pathway with primary OS and new drugs are screened in in vitro systems, new insight about the genetic profiling of OCLs is of paramount importance to a better understanding of the molecular mechanism of this rare tumor and detecting a potential target for specific therapy. Materials and Methods : The SAOS2 and TE85 cell lines were analysed using DNA microarrays containing 19,000 genes. Several genes in which expression was significantly differentially expressed in OCLs vs. normal osteoblast (NO) were detected. Results : The differentially expressed genes cover a broad range of functional activities: (a) cell cycle regulation, (b) cell differentiation, (c) apoptosis, and (d) immunity. Conclusion: The reported data can be relevant to a better understanding of the biology of OS and as a model for comparing the effect of drugs used in OS treatment.